Variance of the Time to Recruitment in an Organization with Two Grades - and V. Vasudevan, A. Srinivasan (Recent Research in Science and Technology, 2011)
<span style="line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; font-size: 11pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;"> In this paper, a two grade organization subjected to random exit of personal due to policy decisions taken by the organization is considered. There is an associated loss of manpower if a person quits. As the exit of personnel is unpredictable, a new recruitment policy involving two thresholds for each grade-one is optional and the other mandatory is suggested to enable the organization to plan its decision on recruitment. Based on shock model approach two mathematical models are constructed using an appropriate univariate policy of recruitment. Performance measures namely mean and variance of the time to recruitment are obtained for both the models when (i) the loss of manhours process forms a sequence of independent and identically distributed exponential random variables (ii) the inter-decision times are independent and identically distributed exponential random variables and (iii) the optional and mandatory thresholds are exponential random variables. The analytical results are substantiated by numerical illustrations and the influence of nodal parameters on the performance measures is also analyzed.